Dietary intake in the dependent elderly: evaluation of the risk of nutritional deficit. Issue 2 (28th April 2015) - Fernández‐Barrés, S.; Martín, N.; Canela, T.; García‐Barco, M.; Basora, J.; Arija, V.; ,
Abstract: Background: Malnutrition is a frequent problem in elderly dependent patients and their prognosis is adversely affected. Assessment of food consumption and adequacy of energy and nutrient intake of dependent elderly is needed to plan any selected actions for this population. Methods: The study comprised a multicentre cross‐sectional study of 190 users (≥65 years) of a home care programme provided by primary care centers in Tarragona (Spain), at nutritional risk (Mini Nutritional Assessment: 17–23.5 points). Food consumption was assessed using a semiquantitative validated food frequency questionnaire. Energy intake was compared with the Spanish dietary reference intake (DRI) and nutritional intakes with the DRI of the American Institute of Medicine. Results: Mean (SD) age was 85.0 (7.2) years (67.5% female). The food items consumed were varied but lower than the recommended portions for cereals, fruits, vegetables and legumes. Energy intake was 7454.2 (1553.9 kJ day –1 ) [1781.6 (371.4) kcal day –1 ] (97.7% of recommended dietary allowance; RDA) and protein intake was 1.0 (0.4) g kg –1 of weight (121.4% of RDA). Proteins provided 13.3%, carbohydrates provided 39.9% and fats provided 45.8% of energy intake. The intakes of calcium, vitamin D, vitamin E and folates were less than two‐thirds of the RDA and their probability of inadequate intake was >85%. Conclusions: Dietary intakes of elderly dependent patients at nutritional risk were well balanced. In general, energy and protein intakes meet the recommendations. The diet was high in energy density, low in complex carbohydrates, high in simple carbohydrates and excessive in fats. The dependent elderly had inadequate intake of micronutrients often related to fragility, such as calcium, vitamin D, vitamin E and folates.